Futures Trading In Pulses, Benefits Whom? - Anuradha, T.; Kavitha, Annie; Davala, Mahitha (Indian Journal of Finance, 2008)
It is appreciated that the government imposed temporary ban on futures trading on some pulses protecting the farmers and the consumers and not leaving the market open to speculative trade like futures trading. It is still beneficial if the trading on pulses as such is banned which will benefit the farmers to grow crops according to the nature of the soil and the seasons and not as per futures trading demand.